La economía popular y solidaria y el desarrollo socioeconómico de los comerciantes del mercado Lizarzaburu (San Francisco) Riobamba - Rivera Solano, Karen Mishel (2024)
ABSTRAC The main objective of this research is to analyze the impact of the popular and solidarity economy on the socioeconomic development of the merchants of the Lizarzaburu market in Riobamba. To achieve this objective, hypothetical-deductive and quantitative methods were used, based on the hypothesis that the popular and solidarity economy has a positive impact on the socioeconomic development of merchants, using surveys as a data collection instrument. The research development is based on the importance of the popular and solidarity economy as an alternative model that seeks to promote social inclusion, equity and sustainable development of merchants and market workers. In addition, the relevance of analyzing its effect in the specific field of market traders who are key players in the local economy is highlighted. The results obtained show that the popular and solidarity economy has had a positive impact on the socioeconomic development of the merchants of the Lizarzaburu market in Riobamba. However, a comprehensive approach is required that addresses the challenges identified to maximize benefits and ensure sustainable and equitable growth, they highlight the importance of promoting and strengthening the popular and solidarity economy as an effective tool to improve the well-being of merchants and contribute to local development in Riobamba.